1972
DOI: 10.1042/bj1290805
|View full text |Cite
|
Sign up to set email alerts
|

The effects of amino acids on albumin synthesis by the isolated perfused rat liver

Abstract: Albumin synthesis was measured in the isolated perfused rat liver by using the livers of both well-fed and starved rats. Starvation markedly decreased albumin synthesis. The livers from starved rats were unable to increase synthesis rates after the addition to the perfusates of single amino acids or the addition of both glucagon and tryptophan. Arginine, asparagine, isoleucine, leucine, lysine, methionine, phenylalanine, proline, threonine, tryptophan and valine, added together to ten times their normal periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(7 citation statements)
references
References 18 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Each value is lower than the estimated nutritional requirement for premature infants (36), although each is typical of the short-term nutritional support offered to infants recovering from hyaline membrane disease and receiving nourishment via a peripheral vein. Substantial evidence from both in vivo and in vitro studies suggests that malnutrition or undernutrition is associated with diminished albumin turnover, not the augmented FSR observed in this investigation (2)(3)(4)(5)(6)(7)(8). The available data suggest that the FSR could have been even greater if the infants had received more amino acids and total calories.…”
Section: Discussionmentioning
confidence: 67%
“…Each value is lower than the estimated nutritional requirement for premature infants (36), although each is typical of the short-term nutritional support offered to infants recovering from hyaline membrane disease and receiving nourishment via a peripheral vein. Substantial evidence from both in vivo and in vitro studies suggests that malnutrition or undernutrition is associated with diminished albumin turnover, not the augmented FSR observed in this investigation (2)(3)(4)(5)(6)(7)(8). The available data suggest that the FSR could have been even greater if the infants had received more amino acids and total calories.…”
Section: Discussionmentioning
confidence: 67%
“…Insulin has been shown to stimulate albumin synthesis both in vitro and in vivo (33,36,37). Although in vivo amino acids may enhance albumin synthesis indirectly by stimulating insulin release, studies performed in isolated perfused liver indicate a direct effect of amino acids on albumin synthesis (12,14). In the study by Volpi et al (3), the stimulation of albumin synthesis in response to insulin was additive to the effect of amino acids.…”
Section: Discussionmentioning
confidence: 83%
“…Many studies, conducted both in animals and humans, have clearly shown that the protein content of ingested nutrients has an important role in the regulation of albumin synthesis, with a decrease in albumin synthesis in response to a reduction in protein intake (4 -11). Indeed, amino acids can have a direct effect on hepatocytes in vitro, up-regulating the synthesis of albumin (9,(12)(13)(14). The ingestion of carbohydrates and fat can also, in the absence of protein, stimulate postprandial albumin synthesis (3), with further enhancement of albumin synthesis in response to the addition of amino acids (3,15).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, actual food intake was not reported in any of the papers discussed. The sensitive response of albumin synthesis to changes in amino acid supply has been confirmed in studies with isolated perfused liver (Gordon, 1966;Rothschild et al, 1968Rothschild et al, , 1969Kirsch et al, 1969;John and Miller, 1969;Hoffenberg et al, 1971;Kelman et al, 1972b). Besides amino acid supply, the concentration of albumin and of hormones in the blood also appear to influence the rate of albumin synthesis.…”
Section: Absolute Rate Of Albumin Synthesismentioning
confidence: 67%